Handbook of seal integrity in the food industry - Dudbridge, Mike (Hoboken, NJ: Wiley Blackwell, 2016)
"Seal integrity is vital in food supply chains with modern methods of food retailing and a requirement for very high levels of consumer satisfaction. Robust packages are an important factor in food preservation, consumer confidence in the product as well as waste minimisation and cost control throughout the system. The Handbook of Seal Integrity in the Food Industry is aimed at people working in food supply chains and associated industries from packing machine operators to quality managers and from retail technical staff to packaging machine designers and maintenance engineers. This well illustrated and comprehensively indexed handbook paints a complete picture of all of the factors that operate together in the creation of food packages with high performing seals. A comprehensive review of the reasons for poor seal integrity is included along with suggestions for improvements in maintenance, machine set up and operation. Seal testing systems are featured along with management techniques to ensure a high level of performance and consistency in your business and a "right first time" approach within packaging systems. The design and operation of the main types of sealing system is reviewed for rigid, semi rigid and flexible packaging systems along with an overview of packing materials such as thermoplastics. Finally the handbook looks at innovations in the packaging of food products with a view of developments in packaging materials, sealing systems and on-line seal integrity measurement and monitoring systems"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Food -- Packaging; Food containers; Sealing (Technology); TECHNOLOGY & ENGINEERING / Food Science; Food containers; Food -- Packaging; Sealing (Technology); Electronic books